Tailoring the secondary coordination sphere: impact of pendent groups on hydrogen evolution in palladium and nickel based calixpyrrole electrocatalysts - Mazumder, Dola (My University, 2026)
The development of efficient and sustainable electrocatalysts for the hydrogen evolution reaction (HER) is essential for advancing clean energy technologies. While platinum-based systems exhibit near-zero overpotential and exceptional catalytic activity, their high cost and limited availability restrict large-scale applications. This work focuses on the rational design of calixpyrrole-based molecular catalysts, emphasizing the role of secondary coordination-sphere modifications in enhancing catalytic performance via proton relay and hydrogen-bonding interactions. Chapter 2 investigates catalyst microenvironments by incorporating proton-shuttling and hydrogen-bond donor functionalities into palladium calixpyrrole complexes. Three complexes bearing pendant amine (2a), amide (2b), and carbamate (2c) groups were evaluated for HER using anilinium tetrafluoroborate as a mild proton source. All systems exhibit homogeneous catalytic behavior. Kinetic studies reveal a second-order dependence on acid concentration and significant H/D kinetic isotope effects, indicating hydrogen decoordination as the rate-limiting step. These catalysts demonstrate exceptional activity, with observed rate constants (k_obs) and turnover frequencies of 4.65 × 10⁶ s⁻¹, 4.19 × 10⁶ s⁻¹, and 3.09 × 10⁶ s⁻¹ for complexes 2a–2c, respectively. These findings establish palladium calixpyrrole systems as benchmarks for ultrafast HER catalysis, rivaling the performance of highly efficient enzymatic systems. Chapter 3 extends this strategy to nickel-based calixpyrrole complexes as cost-effective alternatives. Incorporation of pendant functional groups significantly enhances catalytic performance, lowering the overpotential from 0.96 V in the unsubstituted system to 0.81 V in functionalized complexes. These modifications improve reaction kinetics by facilitating proton-coupled electron transfer (PCET), highlighting the critical role of secondary coordination sphere engineering in optimizing catalytic efficiency. Chapter 4 examines a nickel calixpyrrole complex with a pendant amine in a surface-associated, heterogeneous configuration. The catalyst was deposited on a glassy carbon electrode and evaluated under varying proton-donor strengths using triethylammonium tetrafluoroborate. Electrochemical studies show an increase in catalytic current with acid concentration, reaching an acid-independent regime above 0.075 M, while scan rate analysis confirms a surface-confined process. Controlled-potential electrolysis demonstrates efficient hydrogen production with a Faradaic efficiency of 95.3%, an overpotential of 0.896 ± 0.014 V, and a turnover frequency of approximately 1775 s⁻¹. The pendant amine is proposed to function as a proton relay, facilitating PCET and efficient H–H bond formation. These results highlight the impact of proton-donor strength and interfacial confinement on catalytic behavior. Overall, this work demonstrates that precise tuning of the secondary coordination sphere significantly enhances catalytic activity, lowers overpotential, and improves reaction kinetics in both homogeneous and heterogeneous HER systems. These findings provide important design principles for developing efficient, earth-abundant molecular electrocatalysts for sustainable hydrogen production.
Keywords: Secondary coordination sphere; Hydrogen evolution; Electrocatalysts; Pendent groups; Proton relays and hydrogen bonding